Năng lực marketing số và lợi thế cạnh tranh bền vững: Vai trò trung gian của tính đổi mới sản phẩm và tác động điều tiết của lãnh đạo định hướng tri thức - Đinh Văn , Hoàng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the mediating role of product innovativeness between digital marketing capabilities and sustainable competitive advantage, while evaluating the moderating effect of knowledge-oriented leadership in Vietnamese small and medium enterprises (SMEs). A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) combined with PROCESS Macro was employed to analyze 238 valid responses. Results show that digital marketing capabilities do not directly impact sustainable competitive advantage, but indirectly affect it through product innovativeness. Knowledge-oriented leadership does not moderate the relationship between digital marketing capabilities and product innovativeness, but positively moderates the relationship between product innovativeness and sustainable competitive advantage. The study contributes to digital marketing capabilities theory and proposes managerial implications for enhancing sustainable competitive advantage in SMEs.